Mekanisme Gempa Vulkanik Gunung Talang Pasca Gempa Tektonik Mentawai Tahun 2007-2009, Sumatra Barat - Kriswati, Estu; Pamitro, Y. E.; Basuki, A. (Indonesian Journal on Geoscience, 2010)
DOI:Â 10.17014/ijog.v5i3.104The Mentawai tectonic earthquake (magnitude 6.8 on the Richter Scale) on April 10, 2005 is assumed to trigger Talang volcanic activity that caused an eruption on April 12, 2005. Information on the source mechanism of volcanic earthquakes after the tectonic earthquake is expected to answer question of â€œDo tectonic earthquakes around the Talang Volcano trigger its volcanic activities?â€ Epicenter distribution of the volcanic earthquakes between 2007 and 2009 shows a southeast â€“ northwest pattern with dextral strike-slip fault and normal fault mechanisms. The data show that earthquake activities at the Talang Volcano were dominated by local structure movements influenced by regional tectonic movements. Between 2007 and 2009, there were three process stages related to magnitude 6 or larger tectonic earthquakes around the Talang Volcano. First stage was a period before August 16, 2009. In this stage, volcanic fluids rose to the shallower chamber beneath the Talang Volcano. Second stage was a compressional stage and formation of a reverse fault influenced by Mentawai tectonic earthquake on August 16, 2009 and activation of a fault that intersects the Volcano. The third stage was a compresional stage and formation of a reverse fault influenced by Padang tectonic earthquake on September 30, 2009. In this stage, area fracturing was intensified, thereby the fracturing became more intensive. As the result, the accumulated volume and pressure of several tectonic earthquakes were released that caused an increase of eruption column soon after the tectonic earthquake.